Tumor marker elevations in chronic kidney disease: a retrospective study - You, Liuxia; Xu, Zhongying; Liu, Qiaoling; Jin, Guoming; Wang, Changting (PeerJ, 2025)
Aim To investigate the changes in tumor markers such as carbohydrate antigen 125 (CA125), carbohydrate antigen 153 (CA15-3), carbohydrate antigen 19-9 (CA19-9), carbohydrate antigen 72-4 (CA72-4), pro-gastrin-releasing peptide (proGRP), and human epididymis protein 4 (HE4) in patients with chronic kidney disease (CKD) as compared to healthy individuals, and to analyze the potential indicators that can be utilized for monitoring early renal dysfunction, was the aim of this study. Methods This retrospective study involved 522 participants from our hospital, including 172 patients with CKD and 350 controls. CKD patients were divided into CKD1, CKD2, CKD3, CKD4, and CKD5 stages according to the estimated glomerular filtration rate (eGFR). Plasma creatinine and general clinical data were collected upon admission. Results The level of tumor biomarkers, including carcinoembryonic antigen (CEA), CA125, CA15-3, CA19-9, NSE, proGRP, and HE4, were elevated in patients with CKD (p < 0.05). There were differences in CEA, CA125, CA19-9, NSE, proGRP, and HE4 between the control and CKD groups. The subgroup study showed that CEA, CA15-3, CA19-9, NSE, proGRP, and HE4 were elevated in patients with CKD having normal serum creatinine compared with those in the control group (p < 0.05). ProGRP and HE4 have high predictive values for early renal insufficiency with area under the curve of 0.736 and 0.931, respectively (p < 0.05). Furthermore, HE4 and proGRP were positively correlated with the stages of CKD, with correlation coefficients of 0.623 and 0.712, respectively. Conclusions Patients with CKD have higher tumor markers, some of which are helpful for the early diagnosis of renal impairment.
Keywords: Chronic kidney disease; Tumor biomarkers; Diagnosis